Preparation and biological activity application of single-layer Mo4VC4 nanosheet
Through the peroxidase-like activity catalysis and near-infrared photothermal combination system of single-layer Mo4VC4 nanosheets, the problem of insufficient antibacterial effect of nanomaterials is solved, and efficient antibacterial inhibition and wound healing effects are achieved.
Patent Information
- Application Number
- CN202310373995.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-10
- Publication Date
- 2025-01-07
AI Technical Summary
In terms of antibacterial effects, existing nanomaterials have problems such as poor tissue penetration, low electron transfer efficiency and low photothermal efficiency, and it is difficult to effectively inhibit the infection of drug-resistant bacteria such as methicillin-resistant Staphylococcus aureus.
Using single-layer Mo4VC4 nanosheets as a two-dimensional nanomaterial Mxene catalyst, the production of hydroxyl radicals by peroxidase-like activity is catalyzed with low concentration of hydrogen peroxide, and the high photothermal conversion efficiency under near-infrared light irradiation is used for preparation Antibacterial drugs and therapeutic agents.
It achieves efficient tissue penetration and antibacterial activity, significantly improves the inhibitory effect of drug-resistant bacteria, and enhances the bactericidal efficiency through photothermal therapy, reduces thermal damage to normal tissues, and promotes wound healing.
Smart Images

Figure CN119258091A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of antibacterial bioactivity, and in particular to the study of the inhibitory effect of two-dimensional nanomaterial Mxene catalyst on methicillin-resistant Staphylococcus aureus, specifically involving the synthesis method and application of monolayer Mo4VC4 nanosheets. Background Technology
[0002] Staphylococcus aureus can cause a variety of infections and is resistant to traditional antibiotics. In recent years, substantial progress has been made in the preparation and production of high-quality nanoplatforms to combat this bacterial infection and biofilm formation. These nanoplatforms are particularly effective in addressing the global threat of antibiotic resistance posed by public health sectors.
[0003] Recently, some nanomaterials such as V₂O₅, graphene quantum dots, and Fe₃O₄ have utilized hydrogen peroxide to effectively combat bacterial infections through its peroxidase-like activity. Natural enzymes are primarily proteins, with a small fraction being RNA; they are expensive, time-consuming to produce, and difficult to maintain and store. In contrast, nanozymes, unlike natural enzymes, are not easily digested or denatured by proteases, mimicking and exhibiting enzyme-like activity. They can be categorized into metals, metal oxides, metal sulfides, and carbon-based compounds. The generation mechanism of reactive oxygen species primarily involves peroxidase-like (POD) activity, where low concentrations of hydrogen peroxide are catalyzed to generate highly toxic hydroxyl radicals, which then scavenge bacteria and biofilms. This process avoids resistance. The efficient catalysis of hydrogen peroxide to hydroxyl radicals through a chemical kinetic process has demonstrated several bactericidal activities.
[0004] Transition metal carbides and nitrides (MXenes) are two-dimensional materials characterized by transition metal atoms linked by carbon or nitrogen in a layered array, with the molecular formula Mi. n+1 X n T x In this model, M is a transition metal, X is carbon or nitrogen, T is a functional group, and n = 1-3. MXenes nanoplatforms have attracted increasing attention due to their high hydrophilicity, conductivity, and large surface area distribution, which collectively expand their biomedical applications. MXenes can be effectively used as a chemokinetic nanoplatform to mimic and exhibit enzyme-like activities, representing promising therapeutic conditions for bacteria and for healing infected wounds. Although many nanomaterials have been produced, many suffer from poor bacterial-antimicrobial interactions, low electron transfer efficiency, and low photothermal efficiency. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a method for the preparation and bioactive application of a monolayer Mo4VC4 nanosheet catalyst with deeper tissue penetration and synergistic mild antibacterial properties.
[0006] To achieve the above objectives, the present invention provides a monolayer Mo4VC4 nanosheet, which belongs to the field of antibacterial two-dimensional nanomaterials and Mxene catalysts. It has peroxidase-like activity, can locally catalyze low concentrations of hydrogen peroxide and generate hydroxyl radicals, and can exhibit high photothermal conversion efficiency and photothermal stability under near-infrared light irradiation.
[0007] This invention also provides a method for preparing monolayer Mo4VC4 nanosheets, specifically including the following steps:
[0008] Step 1: Mix Mo4AlVC4 powder and hydrofluoric acid, then wash the product and measure its pH value until the pH value is greater than 6.
[0009] Step 2: Obtain multilayer Mo4VC4 powder through vacuum-assisted filtration and dry the multilayer Mo4VC4 powder.
[0010] Step 3: Disperse the multilayer Mo4VC4 powder evenly in tetramethylammonium hydroxide (TMAOH) to peel off the multilayer Mo4VC4.
[0011] Step 4: Wash the product prepared in Step 3 to remove tetramethylammonium hydroxide and collect the monolayer Mo4VC4.
[0012] Preferably, the method also includes step five, which involves mixing the prepared monolayer Mo4VC4 with polyethylene glycol and stirring at room temperature to obtain modified monolayer Mo4VC4.
[0013] Preferably, in step one, Mo4AlVC4 powder and 40 ml of hydrofluoric acid are mixed until the mixture contains 12.5 g / 100 ml of Mo4AlVC4 powder.
[0014] This invention provides the application of monolayer Mo4VC4 nanosheets, specifically their use in preparing peroxidase-like agents.
[0015] And the use of monolayer Mo4VC4 nanosheets in the preparation of drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors, and subcutaneous drug-resistant bacterial abscess treatment agents.
[0016] Preferably, the drug-resistant bacteria inhibitor is a methicillin-resistant Staphylococcus aureus lysis inhibitor.
[0017] Preferably, the drug-resistant bacteria biofilm inhibitor is a methicillin-resistant Staphylococcus aureus biofilm inhibitor.
[0018] Preferably, the subcutaneous drug-resistant bacterial abscess treatment agent is a subcutaneous methicillin-resistant Staphylococcus aureus (MRSA) abscess treatment agent.
[0019] As a preferred application, the monolayer Mo4VC4 nanosheet combined with NIR photothermal system is used in the preparation of drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors, and subcutaneous drug-resistant bacterial abscess treatment agents.
[0020] Preferably, the monolayer Mo4VC4 nanosheets combined with H2O2 are used to prepare drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors, and subcutaneous drug-resistant bacterial abscess treatment agents.
[0021] Preferably, the monolayer Mo4VC4 nanosheet combined with H2O2 and NIR photothermal combination system is used in the preparation of drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors, and subcutaneous drug-resistant bacterial abscess treatment agents.
[0022] Preferably, all inhibitors and therapeutic agents are irradiated with a 1064nm laser at an intensity of 1W cm⁻¹. -2 Under the following conditions, the effective concentration is 50 μg / mL, the time is 5 minutes, and the hydrogen peroxide concentration is 0.1 mmol.
[0023] The present invention also provides an antibacterial pharmaceutical composition comprising monolayer Mo4VC4 nanosheets and H2O2.
[0024] The present invention also provides a synergistic nano-antibacterial combination system of MXene combined with near-infrared photothermal, comprising a monolayer Mo4VC4 nanosheet and a near-infrared laser.
[0025] Further, this includes monolayer Mo4VC4 nanosheets, H2O2, and near-infrared lasers.
[0026] Furthermore, under irradiation by a 1064nm laser, the intensity is 1W cm⁻¹. -2 The conditions for use were as follows: the effective concentration of Mo4VC4 nanosheets was 50 μg / mL, the time was 5 minutes, and the H2O2 concentration was 0.1 mmol.
[0027] The present invention has the following advantages: the monolayer Mo4VC4 nanosheet nanoplatform based on the two-dimensional nanomaterial Mxene has peroxidase-like catalytic activity, and the simple monolayer Mo4VC4 nanosheet has antibacterial activity.
[0028] Monolayer Mo4VC4 nanosheets possess a unique two-dimensional planar structure, a large specific surface area, and excellent optical and electronic properties. They exhibit outstanding absorption capacity within the near-infrared II biological window, demonstrating highly efficient tissue penetration and effectively overcoming the limitations of low tissue penetration and ROS catalytic activity. Monolayer Mo4VC4 nanosheets can be used in conjunction with photothermal therapy, where near-infrared light irradiation converts light energy into heat energy to kill bacteria.
[0029] Simultaneously, its monolayer Mo4VC4 nanosheets exhibit photothermal absorption in the near-infrared II region, thereby enhancing its photothermal conversion efficiency. Electron excitation under NIR irradiation enhances POD activity by generating reactive oxygen species (PTT), thus enhancing chemokinetic therapy (CDT). Furthermore, its peroxidase-like activity achieves highly efficient photothermal amplification. On the other hand, the application of the two-dimensional nanomaterial Mxene of this invention synergistically generates a highly efficient antibacterial nanoplatform through the combination of photothermal therapy PTT and photothermally enhanced CDT. Inducing effective synergy to improve bactericidal efficiency and reduce drug dosage are some of the advantages enjoyed by various treatment modalities, while avoiding thermal damage to normal tissues.
[0030] Furthermore, the biosafety and antibacterial properties of the monolayer Mo4VC4 nanosheet nanoplatform were systematically evaluated in vivo and in vitro. This work provides a feasible strategy for the effective treatment of wounds infected with methicillin-resistant Staphylococcus aureus (MRSA). Attached Figure Description
[0031] Figure 1 a is a schematic diagram of the synthesis mode of monolayer Mo4VC4 nanosheets in Example 1. Figure 1 bq represents the characterization of the monolayer Mo4VC4 nanosheets in Example 2;
[0032] Figure 2 The photothermal and nanoenzyme properties of the monolayer Mo4VC4 nanosheets in Example 3;
[0033] Figure 3 In Example 4, the monolayer Mo4VC4 nanosheets inhibited Gram-positive and Gram-negative bacteria and inhibited the formation of bacterial biofilms;
[0034] Figure 4 In Example 5, monolayer Mo4VC4 nanosheets inhibited the growth of methicillin-resistant Staphylococcus aureus and promoted wound repair in mice. Detailed Implementation
[0035] The present invention will now be described in further detail with reference to embodiments and effect examples, but this is not intended to limit the scope of the invention.
[0036] Example 1: Synthesis of monolayer Mo4VC4 nanosheets
[0037] Mo4VC4 nanosheets were prepared at 1650 °C with an initial composition of Mo:V:V2O3:Al:C of 4:0.9:0.05:1.2:3.5. As a new member of MXenes, Mo4VAlC4 was transformed from bulk Mo4VAlC4 into "organ-like" multilayer Mo4VC4 through in-situ hydrofluoric acid (HF) etching, followed by ultrasonic exfoliation to obtain monolayer Mo4VC4.
[0038] The specific preparation steps include carefully mixing 5g of Mo4AlVC4 powder and 40mL of hydrofluoric acid (HF), continuously stirring at 400rpm and 50°C, while heating in an oil bath for 8 days. The product was then washed and its pH value was measured until it exceeded 6. The product obtained by vacuum-assisted filtration was collected in a microporous mixed cellulose ester (MCE) membrane (0.45 μm). The product was then dried under the same conditions as described above. The multilayer Mo4VC4 powder was uniformly dispersed in 10mL of tetramethylammonium hydroxide (TMAOH) and stirred at 400rpm and 25°C for 24h to exfoliate the multilayer Mo4VC4.
[0039] Next, a washing step was performed. The product was centrifuged, the alkaline supernatant was discarded, and the resulting particles were resuspended in deionized water. This washing step was repeated five times. The obtained product was centrifuged at high speed, the supernatant was inverted, and the resulting microspheres were resuspended in 30 mL of deionized water. The product was dispersed in deionized water and then centrifuged under ultrasonic treatment at 40 kHz, 100 W, and 1 h. The supernatant was carefully removed with a pipette, and the monolayer Mo4VC4 was collected in a clean bottle. The target monolayer Mo4VC4 was obtained by mixing and modification with polyethylene glycol. 4, This promotes good biocompatibility and dispersibility of the product.
[0040] Example 2 Characterization of monolayer Mo4VC4 nanosheets
[0041] Synthesis of monolayer Mo4VC4 nanosheets as follows Figure 1 As shown. X-ray diffraction patterns of multilayer MXenes and layered Mo4VC4 phases indicate that Mo2C, VC, Al4C3, and Al2O3 may exist in the Max phase (Mo4VAlC4). Figure 1 b). Comparing the X-ray diffraction patterns of the multilayer film and the layered Mo4VC4, it was found that the layered Mo4VC4 lacked most peaks. This is likely a result of the layering, filtration, and drying processes, resulting in a significantly purer Mo4VC4. Figure 1 As shown in c, transmission electron microscopy (TEM) reveals microscopic defects in Mo4VC4MXene attributable to TMOAH intercalation. The selected area electron diffraction (SAED) pattern index is
[001] ( Figure 1 d), showing a layered hexagonal crystal structure, with high-resolution (HR) electron microscopy revealing good crystallinity and a crystal interplanar spacing of 0.264 nm. Figure 1 e). Elemental analysis diagram ( Figure 1f-2j clearly shows the presence of Mo, V, and C components, confirming the uniform distribution of these three elements in Mo4VC4 MXenes, and also showing end groups containing oxygen. Atomic force microscopy (AFM) images show the Mo4VC4 plate thickness to be approximately 3.4 nm. Figure 1 k and 2l). Scanning transmission electron microscopy-energy dispersive X-ray spectroscopy (STEM-EDS) elemental mapping analysis confirmed the presence of (Mo, V, O, and C) atomic layers in the prepared Mo4VC4. Figure 1 m). X-ray electron spectra of Mo3d, V2p and C1s ( Figure 1 n) indicates that Mo(Mo3d) 3 / 2 The binding energy of ) is 228.71 eV, while Mo3d 5 / 2 The binding energies of V2p and C1s are 531.81 eV, 234.98 eV, and 283.53 eV, respectively. Figure 1 This indicates the presence of Mo, V, and C, and the successful etching of Al from the Mo4VAlC4 phase.
[0042] Example 3: Photothermal and Nanoenzyme Properties of Monolayer Mo4VC4 Nanosheets
[0043] Under ultraviolet-visible-near-infrared absorption spectroscopy (UV-vis-NIR), Mo4VC4 exhibits a wide absorption range for NIR-II laser energy, which is directly proportional to the increase in Mo4VC4 concentration. Figure 2 a).
[0044] Further evaluation was conducted on Mo4VC4 at different concentrations (0, 12.5, 25.0, and 50 μg / mL) in the near-infrared II region using a laser (1064 nm, 1.0 W cm⁻¹). -2 Photothermal properties after 6 minutes of irradiation Figure 2 b). The performance of 50 μg / mL Mo4VC4 in the near-infrared II region under different laser power densities (0.25, 0.5, 0.75, and 1.0 W cm⁻¹) was further evaluated. -2 Photothermal performance after 6 minutes of irradiation ( Figure 2 c). The temperature of Mo4VC4 increases significantly with increasing concentration, irradiation time, and laser power density, reaching a maximum at 1.0 W / cm². -2 At this temperature, the concentration of 50 μg / mL increased to 65 °C. This indicates that Mo4VC4 exhibits good photothermal properties under NIR-II light irradiation.
[0045] To further evaluate the photothermal efficiency, the Mo4VC4 suspension was analyzed in the near-infrared II region (1064 nm, 1.0 W / cm²). -2Five heating / cooling cycles were performed at 6 min, and the photothermal performance remained stable throughout the cycle. Figure 2 d). The heating / cooling curves show a photothermal conversion efficiency (η) of 45.5% ( Figure 2 (e and 2f). These results demonstrate that the satisfactory properties of Mo4VC4 can be used in photothermal therapy to significantly convert NIR-II into heat.
[0046] Vanadium is a metal-based nanozyme with important regulatory functions and biocatalytic activity in biological systems. Mo4VC4, with its five transition metal atomic layers, has wide applications in catalysis and contains vanadium, but its application in bacteria in the biomedical field has not been reported. Therefore, the biocatalytic performance of Mo4VC4 was investigated using 3,3',5,5'-tetramethylbenzidine (TMB) and o-phenylenediamine (OPD) as probes, respectively, to monitor hydroxyl radicals and successfully catalyze the formation of blue and yellow (…) compounds in the presence of hydrogen peroxide. Figure 2 g and 2h). The absorbance of TMB at 652 nm increased with increasing Mo4VC4 concentration and near-infrared II exposure (1064 nm, 1.0 W cm⁻¹). -2 (0-35min) and increase ( Figure 2 i). This demonstrates the inherent biocatalytic activity of Mo4VC4 and highlights the improved catalytic efficiency due to enhanced reaction kinetics. Subsequently, the catalytic activity of the catalyst was further evaluated using OPD. Similar phenomena to TMB were observed using the OPD probe ( Figure 2 j) This confirmed and demonstrated the intrinsic biocatalytic activity of Mo4VC4. To further verify that NIR-II can enhance biocatalysis, the activity of Mo4VC4 and the OPD absorption at 420 nm were compared in the presence and absence of NIR-II. Figure 2 As shown in k, the yield of ROS is significantly increased in the presence of NIR-II. Figure 2 Figure 1 illustrates a schematic diagram showing the large amount of reactive oxygen species generated by PTT-enhanced CDT.
[0047] In the presence of Mo4VC4, using TMB and hydrogen peroxide as catalysts, the rate of the hydroxyl radical reaction of hydrogen peroxide was calculated using the Lambert-Beer law, thus determining the steady-state catalytic kinetics of the catalysts. Then, the rate was plotted against the hydrogen peroxide concentration to calculate the Michaelis constant (K). m The maximum speed is 1.49 mM, and the maximum speed is (3.77 × 10⁻⁶ mM). -7 m / s). Low K of Mo4VC4 m This indicates that Mo4VC4 has a better affinity for hydrogen peroxide for high biocatalytic performance or activity.
[0048] In Example 4, monolayer Mo4VC4 nanosheets inhibited the formation of methicillin-resistant Staphylococcus aureus (MRSA) and MRSA biofilms.
[0049] Based on the photothermal effect and biocatalytic activity of Mo4VC4, the in vitro bactericidal effect of Mo4VC4 was evaluated using the plate count method. Methicillin-resistant Gram-positive Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa were selected.
[0050] First, the inhibitory effects of different concentrations (0, 12.5, 25, 50, 100, 200, and 400 μg / mL) of hydrogen peroxide combined with Mo4VC4 on methicillin-resistant Staphylococcus aureus were investigated. The results showed that 0.1 mM hydrogen peroxide was sufficient to produce good antibacterial activity. Since hydrogen peroxide easily affects wound healing efficiency, converting it to ·OH is necessary and convenient, as it can be toxic to bacteria while causing negligible damage to normal tissues.
[0051] Next, the treatment was divided into eight groups: (I) PBS; (II) PBS + NIR-II; (III) H2O2; (IV) H2O2 + NIR-II; (V) Mo4VC4; (VI) Mo4VC4 + NIR-II; (VII) Mo4VC4 + H2O2; (VIII) Mo4VC4 + H2O2 + NIR-II. The concentrations of H2O2 and Mo4VC4 were 0.1 mM and 50 μg / mL, respectively. PBS was used as a control, and NIR-II was set at 1064 nm with a wavelength of 1.0 W cm⁻¹. -2 6 minutes.
[0052] Methicillin-resistant Gram-positive Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa were cultured under the above eight experimental conditions. Figure 3 (a and 3b) PBS; PBS+NIR-II; H2O2; H2O2+NIR-II; and Mo4VC4 groups showed no significant antibacterial activity. However, the Mo4VC4+NIR-II group exhibited some antibacterial activity, killing 73.5% of MRSA. This may be due to the bacteria being exposed to the sharp edges of the NIR-II-enhanced Mo4VC4, leading to the killing of some bacteria. These results indicate that Mo4VC4 has broad-spectrum antibacterial activity, and photothermal or catalytic action alone cannot completely kill bacteria. The bacterial activity of the Mo4VC4+H2O2+NIR-II group was significantly reduced, with a bactericidal rate of 99.5% against MRSA and 99.8% against Pseudomonas aeruginosa. Figure 3 (c and 3d). This indicates that exposure to NIR-II promotes the release of hydroxyl radicals generated from the conversion of Mo4VC4 to H2O2.
[0053] More importantly, scanning electron microscopy (SEM) was used to observe the membrane integrity and morphology of bacteria. Figure 3 (e and 3f). In the PBS; PBS+NIR-II; H2O2; H2O2+NIR-II; and Mo4VC4 groups, Staphylococcus aureus and Pseudomonas aeruginosa exhibited intact morphology, while bacteria in the Mo4VC4+NIR-II, Mo4VC4+H2O2, and Mo4VC4+NIR-II groups showed wrinkling, damage, and collapse, with the most pronounced in the Mo4VC4+H2O2+NIR-II group. In the Mo4VC4+H2O2+NIR-II group, the spherical and rod-shaped morphologies of MRSA and Pseudomonas aeruginosa were completely distorted. This confirms that under NIR-II conditions, Mo4VC4 converts H2O2 into lethal hydroxyl radicals. In summary, these data indicate that bacteria can be inhibited through the photothermal synergistic activity and catalytic action of Mo4VC4 nanozymes.
[0054] Biofilm is a key factor that gradually and persistently leads to antibiotic resistance, severe infections, and delayed wound healing. To further confirm the antibacterial activity of Mo4VC4, the bacterial outer membrane was observed using confocal microscopy. Live / dead staining experiments were performed using SYTO-9 and propidium iodide (PI), with green fluorescence representing live bacteria stained with SYTO-9 and red fluorescence representing dead bacteria stained with PI. Pale red fluorescence was observed in the Mo4VC4+NIR-II and Mo4VC4+H2O2 groups, indicating a certain anti-biofilm effect. Figure 3 g). However, the MRSA biofilm in the Mo4VC4+H2O2+NIR-II group was significantly disrupted, exhibiting deep red fluorescence. Treatment of MRSA under live / dead staining further confirmed the antibacterial, scanning electron microscopy, and antibacterial film results (g). Figure 3 h); MRSA bacteria in the Mo4VC4+NIR-II and Mo4VC4+H2O2 groups were destroyed, with the Mo4VC4+H2O2+NIR-II group showing significant destruction. Subsequently, the crystal violet method was used to quantify the MRSA biofilm. Figure 3 As shown in i and 3j, compared with other groups, the MRSA biofilm in the Mo4VC4+NIR-II, Mo4VC4+H2O2, and Mo4VC4+H2O2+NIR-II groups was significantly damaged. The damage in the Mo4VC4+H2O2+NIR-II group was the most obvious, consistent with the antibacterial test results.
[0055] In Example 5, monolayer Mo4VC4 nanosheets inhibited the growth of methicillin-resistant Staphylococcus aureus and promoted wound repair in mice.
[0056] Inspired by in vitro antibacterial results, the in vivo antibacterial activity of Mo4VC4 was evaluated by establishing subcutaneous abscesses infected with MRSA in Balb / c mice. Figure 4 a) Mice were randomly divided into 4 groups (n=5 per group): (I) PBS; (II) Mo4VC4+H2O2; (III) Mo4VC4+NIR-II; (IV) Mo4VC4+H2O2+NIR-II. The backs of the mice were shaved, disinfected with 75% alcohol, and 100 μL (OD200) was injected subcutaneously. 600 =0.5) bacterial suspension. Subsequently, the PBS group was subcutaneously injected with PBS into the MRSA abscess, the other groups were subcutaneously injected with Mo4VC4, and the Mo4VC4+H2O2 group was subcutaneously injected with 1.0 mM H2O2. Mice in the Mo4VC4+NIR-II group and the Mo4VC4+H2O2+NIR-II group were treated with 1064 nm, 1.0 W cm -2 5 minutes of NIR-II irradiation.
[0057] In the Mo4VC4+NIR-II group, the temperature of Mo4VC4 rose to 55.4℃ within 5 minutes. Figure 4 b).
[0058] like Figure 4 As shown in Figure c, scars were visible in all treatment groups from day 0 to day 3, and then darkened from day 3 to day 10. The Mo4VC4+H2O2+NIR-II group had a significantly lower scar incidence and almost closed wounds, performing better than other groups. This phenomenon was reflected in the bacterial cultures of subcutaneous abscesses in each group. Figure 4 d and 4e).
[0059] Mice in the Mo4VC4+H2O2+NIR-II group experienced a decrease in body weight from day 0 to day 3, but a significant increase from day 3 to day 10. This may be due to the impact of MRSA infection on physiological activity, but the weight stabilized after treatment with Mo4VC4 and NIR-II. Mice in the PBS and Mo4VC4+NIR-II groups experienced a significant decrease in body weight, but returned to normal after day 10. Figure 4 f).
[0060] The wound shrinkage rate was significantly higher in the Mo4VC4+H2O2+NIR-II group (approximately 1.1%), while the rates in the PBS, Mo4VC4+H2O2, and Mo4VC4+NIR-II groups were 59.6%, 21.2%, and 35.7%, respectively. Figure 4 (g). Furthermore, the antibacterial activity evaluations of the PBS, Mo4VC4+H2O2, Mo4VC4+NIR-II, and Mo4VC4+H2O2+NIR-II groups were 99.7%, 35.2%, 55.6%, and 12.5%, respectively. Figure 4(h) This indicates that the photothermal effect cannot completely eradicate MRSA, therefore the mice in these groups had to rely on their immune system for healing, which affected the wound healing rate. In summary, these findings suggest that the combined action of Mo4VC4+H2O2+NIR-II can promote wound healing, and bacterial activity decreases with prolonged healing time.
[0061] In summary, this invention provides an enzyme-mimicking preparation based on monolayer Mo4VC4 nanomaterials. This material exhibits excellent peroxidase-mimicking activity and can be used to prepare enzyme-mimicking preparations with high catalytic activity. This material not only demonstrates good antibacterial activity against drug-resistant Staphylococcus aureus and Pseudomonas aeruginosa in vitro, but also effectively kills Staphylococcus aureus in vivo and promotes wound healing in animals infected with Staphylococcus aureus. In the presence of low concentrations of H2O2, the enzyme-mimicking preparation based on monolayer Mo4VC4 nanomaterials of this invention exhibits excellent in vivo antibacterial activity against Staphylococcus aureus and accelerates wound healing. The monolayer Mo4VC4 nanomaterials provided by this invention are non-antibiotic materials with excellent biocompatibility, which can solve the problem of bacterial resistance caused by antibiotic abuse and have broad application prospects in the preparation of biomimetic materials and antibacterial drugs.
[0062] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention and should not be construed as limiting the specific implementation of the invention to these descriptions. For those skilled in the art, the architectural form of this invention can be flexibly varied without departing from its conceptual framework, leading to the derivation of a series of products. Any simple deductions or substitutions should be considered as falling within the patent protection scope defined by the submitted claims.
Claims
1. An application of a single-layer Mo4VC4 nanosheet, characterized in that: The single-layer Mo4VC4 nanosheet is used for preparing drug-resistant bacteria inhibitors.
2. The use of a single-layer Mo4VC4 nanosheet according to claim 1, characterized in that , the drug-resistant bacteria inhibitors are methicillin-resistant Staphylococcus aureus inhibitors and methicillin-resistant Pseudomonas aeruginosa inhibitors.
3. The use of a single-layer Mo4VC4 nanosheet according to claim 1, characterized in that , the drug-resistant bacteria inhibitor is a drug-resistant bacteria biofilm inhibitor; Or the drug-resistant bacteria inhibitor is a therapeutic agent for abscesses infected with drug-resistant bacteria.
4. The use of any one of the single-layer Mo4VC4 nanosheets according to claim 1-3, characterized in that: Application of the single-layer Mo4VC4 nanosheet combined with the NIR photothermal system in the preparation of drug-resistant bacteria inhibitors; or application of the single-layer Mo4VC4 nanosheet combined with H2O2 in the preparation of drug-resistant bacteria inhibitors; Or the application of the single-layer Mo4VC4 nanosheet combined with H2O2 and NIR photothermal combination system in the preparation of drug-resistant bacteria inhibitors.
5. An application of a single-layer Mo4VC4 nanosheet, characterized in that: The single-layer Mo4VC4 nanosheet is used for preparing a peroxidase-like agent.
6. An antibacterial drug composition, characterized in that: The composition includes a single layer of Mo4VC4 nanosheets and H2O2.
7. A MXene combined with near-infrared photothermal synergistic nano antibacterial combination system, characterized by: It includes a single-layer Mo4VC4 nanosheet and a near-infrared laser.
8. The MXene combined with near-infrared photothermal synergistic nano-antibacterial combination system according to claim 7, characterized in that: It includes single-layer Mo4VC4 nanosheets, H2O2 and near-infrared lasers.
9. The MXene combined with near-infrared photothermal synergistic nano antibacterial combination system according to claim 8, characterized in that: Under 1064nm laser irradiation, the intensity is 1Wcm -2 The conditions used were, the effective concentration of Mo4VC4 nanosheets was 50μg / mL, the time was 5 minutes, and the H2O2 concentration was 0.1mmol.
10. A method for preparing a single-layer Mo4VC4 nanosheet, characterized in that: The steps include: Step 1: Mix and stir Mo4AlVC4 powder and hydrofluoric acid, then wash the product and measure its pH value until the pH value is greater than 6; Step 2, filtering the obtained multi-layer Mo4VC4 powder by vacuum assisted filtration, and drying the multi-layer Mo4VC4 powder; Step 3, the multilayer Mo4VC4 powder is uniformly dispersed in tetramethylammonium hydroxide (TMAOH), and the multilayer Mo4VC4 is peeled off; Step 4: Wash the product prepared in step 3 to remove tetramethylammonium hydroxide, and collect a single layer of Mo4VC4.
Citation Information
Cited By
Silver-doped lanthanum cobalt oxide nanopiezoelectric composite antibacterial materials, their preparation methods and applications
CN122827230A